Socio-economic Aspects of Farmers and Rearing Practices of Village Chicken in Kannur and Kozhikode Districts of Kerala - Kumar, P. Girish; Churchil, R. Richard (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted for a period of four months from January to April, 2019 in Kannur (n=21) and Kozhikode (n=43) districts of Kerala to document the socioeconomic status and poultry rearing practices among the native chicken farming households. The poultry farmers predominantly belonged to Thiya community (95.24 in Kannur and 83.72% in Kozhikode). Poultry rearing was manly undertaken by females (85.71% in Kannur and 90.70% in Kozhikode) with cattle and goat rearing as major livestock rearing activity (23.81% in Kannur and 49.84% in Kozhikode). Most of the native chicken farmers were marginal landholders with less than 50% of land, primarily engaged in small scale business in Kannur (19.05%) or as agricultural labourer in Kozhikode (34.88%). Coconut cultivation was the main agriculture of native chicken farmers in Kannur (52.38%), whereas mixed farming was more common among them in Kozhikode (27.91%). The farmers mostly possessed 5–10 years of experience (28.57 and 34.88% respectively) with birds in their possession were predominantly sourced within the Panchayat (80.96 and 69.77% respectively). The primary purpose of rearing was mainly for both egg and meat (85.71% in Kannur and 60.47% in Kozhikode), while culling of surplus male chicken was done mostly from 6 months to one year (61.90 and 58.14% respectively) and females were allowed to meet natural death (90.48 and 72.09% respectively). The culled males were predominantly used for home consumption (66.67% in Kannur and 41.86% in Kozhikode) or sold out.